Simultaneous analysis of phosphopeptides and intact glycopeptides from secretome with mode switchable solid phase extraction. Issue 41 (7th October 2019) - Chen, Rui; Williamson, Sam; Fulton, Kelly M.; Twine, Susan M.; Li, Jianjun
Abstract : We present a novel method named mode switchable solid phase extraction (MS-SPE) for simultaneous enrichment of phosphopeptides and glycopeptides from the digest of cancer cell secretome. Abstract : We present a novel method named mode switchable solid phase extraction (MS-SPE) for simultaneous enrichment of phosphopeptides and glycopeptides from the digest of cancer cell secretome. This SPE method utilized the electrostatic and hydrophilic affinity of weak anion exchange chromatography and operated sequentially in electrostatic repulsion and hydrophilic interaction chromatography (HILIC) mode to selectively isolate phosphopeptides and glycopeptides from complex samples. With both the protein standard and secretome digest, it was demonstrated that the MS-SPE provided with comparable and complementary performance as the combination of enrichment by conventional metal affinity chromatography and HILIC SPE. The developed method was applied to analyze the secretome of cancer cell line A549 for comprehensive phosphoproteome and glycoproteome analysis. 135 phosphosites and 283 N -glycosites were identified with 2 technical replicates on a Synapt G2 QTOF mass spectrometer. More importantly, this method enabled efficient isolation of phosphopeptides and intact glycopeptides that led to the identification of intact glycopeptides with peptide sequence, N -glycosylation site and glycan compositions. Hence, MS-SPE offers a novel solution for simultaneous analysis of multiple post translational modifications.